Pengaruh metode biblioterapi terhadap perubahan tingkat depresi dan cemas pada pasien kanker payudara di RSUD Arifin Achmad Provinsi Riau: Metode biblioterapi - bayu saputra; Yani Sofiani; Diana Irawati (STIKes Hang Tuah Pekanbaru, 2019)
Patient with breast cancer who get chemotheraphy has an side effect, one of this effect is psychological problem. The psychological problem among breast cancer patient is about depression and anxiety. The implementation of biblioteraphy has a positive effect on psychological condition. The aim of this research was to identify the effect biblioteraphy method on the level of depression and anxiety of breast cancer patient. The method was used quasy experimental pretest-postest with intervention control group design. The sampel was 32 respondents using purposive sampling technique wich divided into 2 groups, the intervention group received biblioteraphy story telling method and pray of Prophet Ayyub Alaihisalam while the control group without intervention.The evaluation of psychological aspect depression and anxiety used Hospital Anxiety Depression Scale (HADS) in bahasa. The analysis of depression and anxiety changes measured using independent t-test. The result: There was a significant relationship between level of depression and anxiety in pre and post on respondents who received intervention and without intervention. Conclusion: the applying of intervention of biblioteraphy method with frequency as much as 5 time and maximum in 45 minutes proved in lowering level of depression and anxiety. It is suggested for applying bibliotheraphy when giving nursing care of breast cancer patient. The future research should investigate other aspect such as education and environment against level of depression and anxiety.